Characterization of Learning, Motivation, and Visual Perception in Five Transgenic Mouse Lines Expressing GCaMP in Distinct Cell Populations - Groblewski, Peter A.; Ollerenshaw, Douglas R.; Kiggins, Justin T.; Garrett, Marina E.; Mochizuki, Chris; Casal, Linzy; Cross, Sissy; Mace, Kyla; Swapp, Jackie; Manavi, Sahar; Williams, Derric; Mihalas, Stefan; et al. (Frontiers in Behavioral Neuroscience, 2020)
To study the mechanisms of perception and cognition, neural measurements must be made during behavior. A goal of the Allen Brain Observatory is to map the activity of distinct cortical cell classes underlying visual and behavioral processing. Here we characterize learning and behavioral performance of five GCaMP6-expressing transgenic lines trained on a visual change detection task. We used automated training procedures to facilitate comparisons across mice. Training times varied, but most transgenic mice learned the task. Motivation levels also varied across mice. To compare mice in similar motivational states we subdivided sessions into over-, under-, and optimally motivated periods. When motivated, the pattern of perceptual decisions were highly correlated across transgenic lines, although performance (d-prime) was lower in one line labeling somatostatin inhibitory cells. These results provide important context for using these mice to map neural activity underlying perception and behavior.